Effectiveness of a tailored medical support to overcome the barriers to education, treatment and good metabolic control in children with type-1 diabetes from ethnic minorities - Iovane, Brunella; Cangelosi, Antonina Marta; Bonaccini, Ilaria; Mastrorilli, Carla; Di Mauro, Dora; Fainardi, Valentina; Chiari, Giovanni; Maltese, Marilena; Caffarelli, Carlo; Vanelli, Maurizio (Acta Biomedica Atenei Parmensis, 2018)
Aim: To analyze the effectiveness of a tailored medical support to help children from ethnic minorities to achieve the same good metabolic control of autochthonous peers with type-1 diabetes (T1D). Methods: Children